THE RELATIONSHIP BETWEEN SELF AWARENESS AND QUALITY OF LIFE IN MENOPAUSE WOMEN : HUBUNGAN SELF AWARENESS DENGAN KUALITAS HIDUP PADA WANITA MENOPAUSE - azhari, nurul aulia; Lestari, Widia; Dilaluri, Ade (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
Women experiencing menopause commonly face both physical and psychological complaints that can disrupt their daily lives. These complaints may reduce the quality of life during menopause. One factor that can influence the quality of life is self-awareness. For menopausal women, self-awareness can help manage personal strengths, weaknesses, motivations, and values. This study aims to analyze self-awareness among menopausal women. It is a quantitative study using a descriptive-correlational method with a cross-sectional approach. The sample consisted of 91 respondents selected through purposive sampling based on inclusion criteria. Bivariate analysis was conducted using the chi-square test. The results showed that self awareness data analysis was categorized as high as 51 respondents (56.0%) and most respondents had a good quality of life as many as 47 respondents (51.6%). Bivariate analysis revealed a significant relationship between self-awareness and quality of life in menopausal women, with a p-value of 0.000 (<0.1). The quality of life and its domains improved with higher self-awareness. Women with high self-awareness tended to have a better quality of life compared to those with low self-awareness in facing menopausal changes. Therefore, increasing self-awareness is essential to support a better quality of life during menopause.